The Beyond Financial Literacy: The Role of Maqāṣid Shariah Literacy and Institutional Trust in Islamic Family Financial Planning - Dea Aryandhana Mulyana Haris; Ulumuddin Nurul Fakhri; Aminah Nuriyah (Faculty of Islamic Business and Management, 2026)
This study examines the influence of Islamic Financial Literacy, Maqāṣid Shariah Literacy, and Trust in Islamic Financial Institutions on Competency in Islamic Family Financial Planning among Muslim households in West Java, Indonesia. A quantitative explanatory approach with a cross-sectional survey design was employed. Data were collected from 200 respondents through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that Maqāṣid Shariah Literacy (β = 0.370, p < 0.001) and Trust in Islamic Financial Institutions (β = 0.455, p < 0.001) significantly enhance Islamic family financial planning competence, whereas Islamic Financial Literacy does not have a significant effect (β = 0.093, p = 0.257). The model accounts for 76.6% of the variance in the endogenous variable, indicating substantial explanatory power. These findings suggest that ethical values embedded in maqāṣid principles and institutional trust are more critical than technical financial knowledge in shaping Islamic financial capability. The study enriches the financial capability literature by emphasizing the role of value-based literacy and institutional confidence in promoting sustainable Islamic household financial management.